Thermal flow and geothermic models of the earth’s crust of the Ukrainian Carpathians - R.I. Kutas (Геофизический журнал, 2014)
Within the limits of the Ukrainian sector of the East Carpathians and adjacent edge of the East European platform thermal flows vary from 35 to 130 mVt/m2. It has been shown on the base of geological-geophysical analysis and mathematical modeling of the heat flow that the principal regularities in distribution of thermal flow are controlled by regional tectonic zoning, which was formed by the process of geological development of the region. Low values of heat flow correspond to the structures with earth’s crust produced in Precambrian and Early Paleozoic (the slope of Precambrian platform and considerable parts of Pre-Carpathian flexure and external flysh Carpathians). Variations of thermal flow within the Folded Carpathians are possibly stipulated by lateral changes of heat generation or heat conductivity within sedimentary layer. High thermal flows in the Pannonian basin are associated with special features of tectonic evolution of lithosphere and earth’s crust during the Alpine stage and with magmatic activity. The increase of thermal flow is conditioned by stretching of the earth’s crust and lifting of asthenosphere.